Development and Evaluation of a PCB‘s Manual Assembly system using Augmented Reality and Total Quality - Bauer, Rudieri Dietrich; Watambak, Thiago Luiz; Agati, Salvador Sergi; Hounsell, Marcelo da Silva; da Silva, Andre Tavares (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2021: Anais do XXIII Simpósio de Realidade Virtual e Aumentada, 2021)
Manual assembly remains an important step for many products manufacturing and it is responsible for employing many workers. Nevertheless, manual assembly is susceptible to human errors. Augmented Reality (AR) is one of the enabling technologies to industry 4.0, which has the potential to help by providing on-demand guidance and support monitoring features that comply with Total Quality Management (TQM). Based on these assumptions, the Augmented Reality for Manual Assembly system (RAMM) was developed as an AR system to help PCB‘s manual assembly. A questionnaire was submitted to 124 evaluators. The answers raised questions about the system interface, the devices’ usability and the possible long-term implications of using RAMM. They also found that the software would benefit the assembly of Printed Circuit Boards (PCBs) in many aspects, such as reducing errors, improving quality, novices training, and the way that information resources are presented to the assembler. The functionalities of the system were positively evaluated, which resulted in an overall score of 8.14 (on a scale from 0 to 10). The conclusion is that the RAMM system was able to satisfactorily integrate AR functionalities identified for PCBs assembly, following the principles of TQM and thereby helping to improve the process of manual assembly of PCBs.